Acute and late outcomes of transcatheter aortic valve implantation (TAVI) for the treatment of severe symptomatic aortic stenosis in patients at high- and low-surgical risk - Schymik, Gerhard; Süselbeck, Tim (Journal of interventional cardiology, 2012)
Background: This prospective study examines the impact of EuroSCORE and transfemoral (TF) or transapical (TA) delivery approach on mortality at 30 days and 1 year in patients with severe aortic stenosis implanted with either the Edwards SAPIEN Transcatheter Heart Valve (THV) or Medtronic CoreValve. Methods and Results: TAVI was successfully performed in 293 (97.7%) of 300 patients (TF: 174, TA: 126, mean EuroSCORE 24.0). The mortality at 30 days and after 1 year was 6.0% and 17.3%. Mortality depends significantly on the logistic EuroSCORE with a 30-day odds ratio (OR) of 1.92 (95% CI 1.41 to 2.62, P < 0.001) and after 1 year of 1.67 (95% CI 1.34 to 2.08, P < 0.001). Mortality in patients with a logistic EuroSCORE <15 (n = 113) or ≥15 (n = 187) at 30 days was 0.9% versus 9.1% and after 1 year 7.1% versus 23.5% demonstrating significantly less mortality (P < 0.001) in patients with lower logistic EuroSCOREs. In this specific setup of our center there was no significant difference (P = 0.553) in mortality regarding the technical approach for TA (4.0% and 15.9%) and for TF (7.5% and 18.4%). Severe cardiac complications occurred in 20 patients (6.7%) with a 30-day mortality of 45.0%. Conclusion: The mortality in patients undergoing TAVI correlates significantly with the logistic EuroSCORE. Patients with a logistic EuroSCORE <15 can be implanted, with a low 30-day mortality and good long-term outcome over 1 year. (J Interven Cardiol 2012;25:364-374)